The Effectiveness of SCIDOTS to Reduce Smoking Behavior Among Patients with Pulmonary Tuberculosis : Systematic Review - Supriatin, Eva; Nurhayati, Nunung; Lindayani, Linlin (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : The aim of this study is to identify and summarize the results of previous studies on the use of SCIDOTS to reduce smoking cessation in patients with pulmonary tuberculosis. Methods : The research used was a literature review of three articles. The assessment of the articles shall be measured using the CASP (Critical Appraisal Skills Program) format. Results : The result of this study incorporating smoking cessation programs into pulmonary TB control programs, as new diagnoses can increase cessation rates by 71.7%. Various interventions, including counseling sessions, behavioral therapy, and health promotion programs, have proven successful. Conclusions : The study found that the intervention SCIDOTS, or quitting smoking, is highly effective in treating tuberculosis patients, accelerating their active treatment.